Linear algebra - Shen, Li-Yong; Wang, Haohao; Wojdylo, Jerzy (Mercury Learning & Information, 2019)
The aim of this book is two-fold: to introduce the fundamental concepts of linear algebra and to apply the theorems in computation-oriented applications. The book is suitable for a one semester course in linear algebra that can be used in a variety of contexts. The presentation of the material combines definitions and proofs with an emphasis on computational applications, providing examples that illustrate the use of software packages such as Mathematica®, Maple®, and Sage. Features:- Introduces the fundamental concepts of linear algebra and applies the theorems in computation-oriented applications- Presents a brief introduction of some aspects of abstract algebra that relate directly to linear algebra, such as groups, rings, modules, fields and polynomials over fields.